The infamous Ganoderma disease / Muhammad Aidil Ibrahim - Ibrahim, Muhammad Aidil (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Palm oil production is found to be very important in developing countries and the trees, Elaeis guineensis were grown throughout the Asian countries primarily in Southeast Asia. Palm oil production has been one of the biggest contributors to the Malaysian economy. In fact, in 2008, about 50% of the palm oil production in the world was produced by Malaysia, and hence, counted as the world's largest palm oil producer and exporter. Unfortunately, there are some factors that may hold back the success of the palm oil industry which is fungus attack mainly by Ganoderma boninense. This serious fungal attack can cause Basal stem rot (BSR) where the base of the oil palm tree is infested with fungus and eventually causing it to rot and collapse. In the past 80 years, BSR was known as the most destructive disease of oil palm plantations and caused a severe economic loss in Southeast Asia mainly in Malaysia and North Sumatra. There are many species of fungi that can infect and cause diseases to plants and crops which have elevated the concern of many authorities. However, the main oil palmd isease in Malaysia is Ganoderma disease that causes basal stem rot (BSR).